Growth and Impact of Mutual Funds: Some Analytical and Public Policy Issues: Discussion - Ketchum, Marshall D.; Clendenin, John C.; Richardson, Dorsey (Journal of Finance, 1963)
Marshall D. Ketchum, John C. Clendenin, Dorsey Richardson, Growth and Impact of Mutual Funds: Some Analytical and Public Policy Issues: Discussion, The Journal of Finance, Vol. 18, No. 2 (May, 1963), pp. 392-403